Autocad 2014 for dummies - Fane, Bill; Byrnes, David 1947- (2013)
Put away that pencil and paper and start putting the power of AutoCAD 2014 to work in your CAD projects and designs. From setting up your drawing environment to using text, dimensions, hatching, and more, this guide walks you through AutoCAD basics and provides you with a solid understanding of the latest CAD tools and techniques. You'll also benefit from the full-color illustrations that mirror exactly what you'll see on your AutoCAD 2014 screen and highlight the importance of AutoCAD's Model view, which shows different line weights for printing in different colors.
Getting started with AutoCAD 2014. Introducing AutoCAD and AutoCAD LT ; The grand tour of AutoCAD 2014 ; A lap around the CAD track ; Setup for success ; A zoom with a view -- Let there be lines. Along the straight and narrow ; Dangerous curves ahead ; Preciseliness is next to CADliness ; Manage your properties ; Grabbing onto object selection ; Edit for credit ; Planning for paper -- If drawings could talk. Text with character ; Entering new dimensions ; Down the hatch! ; The plot thickens -- Advancing with AutoCAD. The ABCs of blocks ; Everything from arrays to xrefs ; Call the parametrics! ; Drawing on the internet -- On a 3D spree. It's a 3D world after all ; From drawings to models ; It's showtime! -- The part of tens. Ten AutoCAD resources ; Ten system variables to make your AutoCAD life easier ; Ten AutoCAD secrets.
Includes index.
AFN Regalado (Recommending faculty) AY2016-2017
Keywords: AutoCAD; Computer-aided design